2018
DOI: 10.1523/jneurosci.1254-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortex Excitability Reflects the Subjective Value of Reward and Mediates Its Effects on Incentive-Motivated Performance

Abstract: Performance-based incentives tend to increase an individual's motivation, resulting in enhancements in behavioral output. While much work has focused on understanding how the brain's reward circuitry influences incentive-motivated performance, fewer studies have investigated how such reward representations act on the motor system. Here we measured motor cortical excitability with transcranial magnetic stimulation while female and male human participants performed a motoric incentive motivation task for prospec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 62 publications
2
33
0
Order By: Relevance
“…While spinal stretch reflex is extremely fast, it is difficult to assume an effect of reward or motivation occurring at the spinal level. On the other hand, transcortical feedback includes primary motor cortex processing (Pruszynski et al, 2011), a structure that shows sensitivity to reward (Bundt et al, 2016; Galaro et al, 2019; Thabit et al, 2011). Consequently, an exciting possibility for future research is that transcortical feedback gain is directly enhanced by the presence of reward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While spinal stretch reflex is extremely fast, it is difficult to assume an effect of reward or motivation occurring at the spinal level. On the other hand, transcortical feedback includes primary motor cortex processing (Pruszynski et al, 2011), a structure that shows sensitivity to reward (Bundt et al, 2016; Galaro et al, 2019; Thabit et al, 2011). Consequently, an exciting possibility for future research is that transcortical feedback gain is directly enhanced by the presence of reward.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a saccade task, reward reduced participant’s reaction time whilst making them less sensitive to distractors (Manohar et al, 2015). It has also been shown that reward invigorates movement execution by increasing peak velocity and accuracy during saccades (Manohar et al, 2015; Takikawa et al, 2002) and reaching movements (Carroll et al, 2019; Galaro et al, 2019; Summerside et al, 2018). Therefore, this body of work suggests that reward can consistently shift the speed-accuracy function, at least in isolation, of both selection and execution.…”
Section: Introductionmentioning
confidence: 99%
“…Additional TMS work demonstrated an increase in motor cortex excitability during motor preparation in anticipation of reward delivery, thus providing compelling evidence for an involvement of M1 in reward-guided motor processing [21,22]. This effect could be mediated by ventral striatal reward circuitry, given its established role in instrumental learning for reward [45,46].…”
Section: Role Of Frontopolar Cortex In the Intentional Modulation Of mentioning
confidence: 92%
“…Nineteen right-handed participants (10 females, mean = 27.7 yrs, std = 3.3 yrs, range [21][22][23][24][25][26][27][28][29][30][31][32][33] with no musical training were recruited. Laterality quotient was assessed by the Oldfield handedness inventory ( [49]; mean = 90, SEM = 3.2; values available in 17/19 participants).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation